“Through the Things That Have Happened to Me, They’ve Made Me Stronger”: Individual and Interpersonal Sources of Violence and Resilience Among a Diverse Sample of Transgender Women in Los Angeles - Winiker, Abigail K. (Journal of interpersonal violence, 2023)
Within the United States, transgender women face a disproportionate burden of violence, experiencing increased rates of multiple forms of violence compared with cisgender women and other sexual/gender minority groups. Among transgender women, further racial/ethnic disparities in experiences of violence exist. Resilience has been shown to be protective against the adverse impacts of violence on mental and physical health outcomes, yet little is known about unique sources of resilience, coping, and strength among transgender women. Sixteen in-depth interviews were conducted with a racially diverse sample of transgender women between May and July, 2020 in Los Angeles. Participants were between the ages of 23 and 67 years. Four participants identified as African American/Black, four as Latina, four as White, two as Asian, and two as Native American. Participants were recruited from a local social service organization. Interview questions assessed social network characteristics, experiences of violence, coping mechanisms, and sources of resilience in response to violence. Deductive and inductive coding schemes were used to identify common themes, and data analysis focused upon experiences of violence and sources of resilience/coping. Violence was common among members of the sample, with every participant reporting a history of multiple forms of violence. Violence perpetration came from many sources, including cisgender male strangers, family members, intimate partners, and other transgender women. Women also reported multiple sources of strength and coping, including engaging in self-care and leisure activities, behavioral adaptations, mentorship/support from other transgender women, and striving to “pass” as cisgender. Despite having faced extensive violence, the participants in this sample were resilient, demonstrating many internal and external coping mechanisms and sources of strength. These findings can inform programs and services that target transgender women, providing participants with opportunities to build resilience and other coping mechanisms to buffer the harmful mental and physical health impacts of exposure to violence.